TRUST AND EFFICIENCY OF THE PUBLIC SECTOR: THEORETICAL ASPECTS OF INTERRELATION - Brychko, Maryna (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The issue of trust in government and its efficiency has been a controversial and much-disputed subject within economics, sociology, and public sector management. This study presents a systematic literature review of trust research undertaken with regard to government, its performance (efficiency), and the quality of public services. Theoretical and methodological principles of the interrelations between trust and efficiency of the public sector of the economy are analyzed and deepened, based on the fundamental provisions of the theories of micro- and macro-efficiency. The article considers the concept of trust in the public sector of the economy as one of the main intangible resources that can be used by the state in order to achieve socially and economically beneficial as well as public valuable outcomes. The duplex relationship between trust and efficiency of the public sector is proved, according to which trust is both a condition and a result of the government institutions functioning and services providing. Generalization of key characteristics of the main indicators of state efficiency within the concepts of micro- and macro-efficiency allowed identifying several groups of indicators based on subjective and objective assessment of economic efficiency of the state. Objective indicators that determine the economic development of the country, which is the basis of the quality of citizens’ life, and forms the level of their satisfaction and trust in the state and its institutions, include monetary indicators of macroeconomic efficiency of the state and indicators that characterize public finance and income inequality in the country. Subjective assessment of the economic efficiency of the state, the work of its institutions and the quality of public services includes sociological surveys and quantitative indicators based on self-assessment by economic agents based on their own beliefs, knowledge, life values and worldview, cultural, ethnic, religious, ideological norms, as well as previously accumulated personal life experience of intercommunion with state institutions.